2016
DOI: 10.1175/ei-d-15-0012.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Winter Mortality Variability in Five Regions of England Using Back Trajectory Analysis

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 96 publications
(96 reference statements)
2
13
0
Order By: Relevance
“…Similar is the pattern for the Southeast (Table 2), the West Midlands (Table 3), the Yorkshire and Humber (Table 4) and the Northeast region (Table 5), where classes C6 and C8 presenting the lowest maximum/minimum temperatures are linked with the highest PI values (figures not shown). This finding is in agreement with results provided by Dimitriou et al (2016) who defined atmospheric pathways linked with winter low temperature episodes (LTE) in the same 5 regions of England for the same time period and revealed associations with excess mortality rates. According to them, a statistically significant increase in mortality was calculated for LTE days across all 5 regions studied.…”
Section: Presentation Of the Classessupporting
confidence: 93%
See 3 more Smart Citations
“…Similar is the pattern for the Southeast (Table 2), the West Midlands (Table 3), the Yorkshire and Humber (Table 4) and the Northeast region (Table 5), where classes C6 and C8 presenting the lowest maximum/minimum temperatures are linked with the highest PI values (figures not shown). This finding is in agreement with results provided by Dimitriou et al (2016) who defined atmospheric pathways linked with winter low temperature episodes (LTE) in the same 5 regions of England for the same time period and revealed associations with excess mortality rates. According to them, a statistically significant increase in mortality was calculated for LTE days across all 5 regions studied.…”
Section: Presentation Of the Classessupporting
confidence: 93%
“…In the presence of various confounding factors, it can be the slightly higher temperatures that are linked to excess mortality. Furthermore, Dimitriou et al (2016) concluded that in some cases mortality in the 5 regions studied is linked to rather increased winter temperatures associated with longdistance west-to-east flows, resulting in rapidly changing weather, as opposed to stable conditions linked with blocking to the east. Rapidly changing atmospheric pressure and/or temperature have been longed blamed for adverse health effects.…”
Section: Presentation Of the Classesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutritional factors include major and trace dietary elements, vitamins, unsaturated fatty acids, and so forth. In the elderly, extreme temperatures have a significant impact on mortality [ 1 , 2 , 3 , 4 , 5 , 6 ], and exposure, or lack of exposure, to the climatic change often prompts long-term effects of harsh winters can contribute to differences in mortality among these individuals [ 7 ]. Hypoxia induced by living at higher altitudes affects health and disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%